Oral hygiene practices and periodontal disease status assessment among diabetic patients from three selected public medical primary care clinics in Kuantan, Malaysia - Tin, Myo Han; Ismail, Razida; Yaacob, Munirah; Md Aris, Mohd Aznan; Osman, Iskandar Firzada; Sidek, Sorayah; Thuraiapprah, Mahendran; Abdullah, Fa’iza; Than, Tun Sein; Saub, Roslan (International Islamic University Malaysia, 2016)
Evidences on the bilateral relationship between diabetes mellitus (DM) and periodontal disease (PD). Thus, the aim of this study was to assess periodontal disease status and oral hygiene of DM-patients from public medical care clinics (PMPCCs.